Agricultural Waste Residues as Potential Sources of Bioethanol - Pokhrel, Chandra Prasad; Yadav, Ram Kailash Prasad; Ohga, Shoji (Scientific World, 2010)
The most common renewable fuel today is ethanol derived from corn grain (starch) and sugar cane (sucrose). It is expected that there will be limits to the supply of these raw materials in the near future as well as these are directly associated with food security. Therefore, lignocellulosic biomass is seen as an attractive alternative feedstock for the future supplies of bioethanol. Technologies are being developed that will allow cost-effective conversion of biomass into fuels and chemicals. About 491 GL of bioethanol might be produced from the wasted crops and their associated lignocellulosic raw materials, about 16 times higher than the current world ethanol production (31 GL). Key words: Bioethanol; Lignocellulosic material; Biofuel; Agricultural residue. DOI: 10.3126/sw.v6i6.2628 Scientific World, Vol. 6, No. 6, July 2008 19-23